Best Wishes : Time After Time - Book 3 - Mlynowski, Sarah; Soontornvat, Christina (New York : Scholastic Press, 2023)
"In this book, written by bestselling author Sarah Mlynowski and three-time Newbery Honor recipient Christina Soontornvat, the magic bracelet comes to a girl in Texas, who ends up in a Groundhog Day-style time loop."--
Ages 8-12.
Grades 4-6.
Keywords: Wishes -- Juvenile fiction; Magic -- Juvenile fiction; Friendship -- Juvenile fiction; Schools -- Juvenile fiction; Wishes -- Fiction; Magic -- Fiction; Friendship -- Fiction; Schools -- Fiction; Diaries -- Fiction; Texas -- Juvenile fiction; Texas -- Fiction; Magic realist fiction; Diary fiction; Fantasy fiction; Humorous fiction